Meningkatkan Motivasi Belajar IPA Melalui Pemanfaatan Lingkungan Sekolah Sebagai Sumber Belajar Di SDN Lagoa 05 - Toaini, Toaini (Universitas Cokroaminoto Yogyakarta, 2023)
This research is to examine the importance of increasing motivation to learn science in class V SDN Lagoa 05 North Jakarta through the use of the school environment as a learning resource. This research is an action research study, which is carried out in class, so it is commonly called Classroom Action Research (CAR). The results showed that there had been an increase in student learning motivation by utilizing the school environment as evidenced by the increasing percentage of motivation from the questionnaire distributed to 40 respondents from each cycle, namely 70.59% in cycle I, which means it was still below the target, and in cycle II the results achieved were 81.73%. Utilization of the school environment in learning can increase student learning motivation, because students become more stimulated to learn better.